Laos’ hydropower development and cross-border power trade in the Lower Mekong Basin: a discourse analysis - Thong Anh Tran; Suhardiman, Diana (Wiley, 2020)
Increasing demands for energy to boost the Mekong economies have attracted the keen interest of riparian countries for hydropower development. This is evidenced by extensive investment in hydropower projects across the region over the last few decades. Drawing on interviews with key stakeholders, including officials from Ministry of Energy and Mines, Ministry of Natural Resources and Environment, Ministry of Agriculture and Forestry, private sector actors, civil society organisations and academics, as well as secondary data from public and policy resources, this paper aims to examine how the government of Laos’ (GoL) decisions in hydropower development are influenced by regional energy dynamics, and how these shape the country’s future energy development. The paper argues that the GoL’s decisions on hydropower development are highly dilemmatic, given the current limited institutional capacity in hydropower governance and the accelerating evolution of alternative energy in neighbouring countries. While uncertainty in power markets is recognised, this places greater pressure on new hydropower projects as to how much power could be sufficiently produced and exported. The paper calls for GoL’s policy considerations on the development and planning of alternative energy to secure the sustainable and equitable use of water resources as stipulated in the 1995 Mekong Agreement.